Chain stiffness regulates entropy-templated perfect mixing at single-nanoparticle level. Issue 2 (14th December 2015) - Huang, Zihan; Lu, Ce; Dong, Bojun; Xu, Guoxi; Ji, Chengcheng; Zhao, Kongyin; Yan, Li-Tang
Abstract : We have described for the first time the insights gained from a CGMD study of entropy-templated mixing regulated by chain stiffness. Abstract : The mixing on a single-particle level of chemically incompatible nanoparticles is an outstanding challenge for many applications. Burgeoning research activity suggests that entropic templating is a potential strategy to address this issue. Herein, using systematic computer simulations of model nanoparticle systems, we show that the entropy-templated interfacial organization of nanoparticles significantly depends on the stiffness of tethered chains. Unexpectedly, the optimal chain stiffness can be identified wherein a system exhibits the most perfect mixing for a certain compression ratio. Our simulations demonstrate that entropic templating regulated by chain stiffness precisely reflects various entropic repulsion states that arise from typical conformation regimes of semiflexible chains. The physical mechanism of the chain stiffness effect is revealed by analyzing the entropic repulsion states of tethered chains and quantitatively estimating the resulting entropy penalties, which provides direct evidence that supports the key role of entropic transition in the entropic templating strategy, as suggested in experiments. Moreover, the model nanoparticle systems are found to evolve into binary nanoparticle superlattices by remixing at extremely high stiffness. The findings facilitate the wide application of the entropic templating strategy in creating interfacially reactive nanomaterials with ordered structures on the single-nanoparticle level as well as mechanomutable responses.